Al-Qawa'id al-Fiqhiyyah al-Khams: Lima Kaidah Pokok Fikih sebagai Landasan Penetapan Hukum Islam - Nur Ainun Faizah; Salsabila Nur Syamsuddin; Nur Cahyani; Mulfizan M; Besse Ruhaya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Qawa'id al-Fiqhiyyah are general legal principles formulated by Islamic scholars based on the Qur'an, Hadith, and the results of ijtihad to serve as guidelines for understanding and establishing Islamic law. This study aims to examine the five major legal maxims (Al-Qawa'id al-Fiqhiyyah al-Khams), namely Al-Umuru bi Maqasidiha, Al-Yaqinu La Yuzalu bi al-Syakk, Al-Masyaqqatu Tajlibu al-Taysir, Al-Dhararu Yuzal, and Al-'Adatu Muhakkamah, including their legal foundations, functions, applications, and the differences of opinion among scholars regarding each maxim. This research employs a library research method using a descriptive qualitative approach through the analysis of classical and contemporary literature in the fields of fiqh and ushul fiqh. The findings indicate that these five major legal maxims constitute the primary foundation for the development of other fiqh principles and play a significant role in the process of istinbath (legal reasoning) in Islamic law. Their application enables scholars to address various emerging legal issues systematically while remaining consistent with the principles of Islamic law. Although differences of opinion exist among the schools of Islamic jurisprudence concerning the scope and application of these maxims, such differences demonstrate the flexibility of Islamic law in responding to contemporary issues. Therefore, a thorough understanding of Al-Qawa'id al-Fiqhiyyah al-Khams is essential for supporting the formulation of legal rulings that are just, systematic, and aligned with the objectives of Islamic law (maqasid al-shariah).